Implikasi Penggunaan Alih Kode Dalam Film “Ngeri-Ngeri Sedap” Terhadap Komunikasi Antar Remaja di Lingkungan Sekolah - Aura Meriska; Felicia Joice Sitinjak; Inge Irawati; Yuliana Sari (Universitas Palan, 2024)
Language diversity allows each person to use more than one language. The use of several languages ​​in communication presents the potential for code mixing and code switching. These two linguistic events often occur in various environments, even in the mass media. This study aims to describe (1) the types and forms of code switching in the film Ngeri Ngeri Sedap; (2) factors that cause code switching in the film Ngeri-Ngeri Sedap; and (3) the use of the analysis results as a review of communication between teenagers in the school environment. This study is a qualitative descriptive study. The data collection technique used is the free listening technique with advanced techniques in the form of note-taking techniques. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) there are 15 internal code switching data involving Indonesian, Batak, Sundanese, and Javanese. (2) the results of the analysis can be used as a review of communication between teenagers in the school environment.